DEVELOPMENT OF SKILLS OF FOREIGN LANGUAGE TEACHERS IN WORKING WITH GRANTS (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The development of foreign language teachers’ skills in working with grants is crucial for enhancing educational opportunities and professional growth. This article explores the key competencies required for successful grant writing, project management, and implementation in the field of language education. It highlights the challenges teachers face and provides recommendations for effective training programs. The study emphasizes the role of international cooperation and financial literacy in grant-related activities, ultimately contributing to the advancement of language education.